Trabalho intensificado e os transtornos mentais comuns em docentes de uma universidade pública na Bahia - Azevedo, Caroline Almeida de (2017)
The intensification of work is seen to be an ongoing concept, mainly for methodological complexity involved attempting to solidify theoretical basis capable ofassessing and measuring issues related to work demands on physical, psychological and emotional areas. Thus, this essay aims: to analyze the relationship between intensification of work and CMD in teachers from a public university in Bahia; to establish indicators for intensified work in university teaching; and to assess associated factors regarding intensification of work amongteachers from a public university in Bahia. It consists of four scientific articles: 1- Reflections on teachers’ health in the context of commodification of higher education; 2- Intensified work among higher education teachers: construction of measurement indicators; 3- Caracterization of intensified work among teachers at a public university in Brazil ; 4- Association between intensified work and common mental disorders in teachers. Taking into consideration the high number of academic productivity, accounted for the material and immaterial workday combined with the set of relationships established on the work environment are conditions that may cause illnesses and/or worsen the workers’ health. Common Mental Disorders are presented as potentialillnesses in face of the intensified work. This is anepidemiologic cross-sectional study performed by collecting data through a self-administered structured questionnaireapplied to representative samples of randomly selected university teacher. Regarding the association assessment, the CMD’s are considered to be variable outcomes. The present study may identifyindicators of work intensification in university teaching, contributing to produce empirical evidences and possible relevant analysis. Therefore, this survey may give supportto health and safety measures for such professionals, besides promoting changing actions in the university work context.